Sistem Informasi Sarana dan Prasarana Pada Dinas Lingkungan Hidup Kabupaten Langkat - Delya Putri Maharani; Raheliya Br Ginting; Siti Jamilah Br Tarigan (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
In the management of the facilities and infrastructure system at the Environment Agency, computerized systems such as Microsoft Word and Microsoft Excel have been used to manage facilities and infrastructure data. However, this method still has many drawbacks, such as making it difficult to search for data and can make it vulnerable to losing data facilities and infrastructure if the computer device is damaged or lost, so that it can make it difficult for the agency to re-record again. The purpose of this research is to produce an information system for the management of facilities and infrastructure data at the Langkat Regency Environmental Office. can provide faster and more accurate information to those who need it. and can make it easier and save time in obtaining information on facilities and infrastructure at the Environment Agency. Research Methods Using data collection techniques in the form of Observation, Interviews, Documentation and Literature Studies and the system development tools using Flowcharts, DFD and ERD. The website-based Facilities and Infrastructure Information System at the Langkat Regency Environment Office is very helpful. With this system, all data on the management of Facilities and Infrastructure can be managed more neatly and easily. This system can also make work easier to be faster and more efficient because all data can be accessed anytime and from anywhere